MANAJEMEN WAKAF PRODUKTIF DI YAYASAN MADRASAH ISLAMIYAH (YMI) WONOPRINGGO KABUPATEN PEKALONGAN - Ubaidillah Ubaidillah; Minati Maulida; Muhammad Zakki Mubarok (Fakultas Ekonomi dan Bisnis Universitas Pekalongan, 2024)
Management is a comprehensive and gradual process intended to realize a strategy that can be said to be effective. The management process includes 4 functions of management itself, namely planning, organizing, leadership and controlling. Based on the background above, the author is interested in conducting research related to productive waqf management by implementing management functions at the Madrasah Islamiyah Foundation. The target of this research is to find out how productive waqf management is implemented and the problems that occur in productive waqf management at the Madrasah Islamiyah Foundation. This research was conducted at the Wonopringgo Madrasah Islamiyah Foundation by taking three informants. This research use desciptive qualitative approach. The techniques used are interviews, observation and documentation. The research results show that productive waqf management at the Wonopringgo Madrasah Islamiyah Foundation, Pekalongan Regency is quite good but not yet optimal, seen from every existing activity and work program that has implemented management functions such as planning, organizing, implementing and supervising. The problems of managing productive waqf at the Madrasah Islamiyah Foundation include, firstly, administrative problems, secondly the productivity of productive waqf, the quality of the nadzhir human resources, and finally the condition of the waqf land.